MODERN LAW ENFORCEMENT AGENCIES OF UKRAINE:: REFORM PROBLEMS AND DEVELOPMENT PROSPECTS - H. Lukashevych, Vitalii; V. Deev, Maxym; V. Kaliuga, Karina; V. Uzunova, Oksana; O. Rud, Darina (Revista Gênero e Interdisciplinaridade, 2020)
The legal system of Ukraine is in a state of reform due to the establishment of a democratic, social, rule of law society. The above mentioned necessitated a rethinking and proper reformation of all public authorities, including law enforcement agencies. The subject of the research is the analysis of problems of modern law enforcement agencies in the genesis of their formation and development. The purpose of the article was specified in the tasks in the following areas: analysis of the current state of the law enforcement system, highlighting the problems of their reform, scientific forecasting of prospects for improvement. The theoretical and legal features of law enforcement activities were adopted as a methodological basis of the research as a type of law enforcement activity, which constitutes the relevant state institutions – law enforcement agencies. Their activities were investigated in the main legislatively recognized areas. As a result, it made it possible to distinguish a list of their characteristic features: state-power specificity; legality; the enforceable nature of the decisions made; the use of coercion.